Soviet Statistics of Physical Output of Industrial Commodities: Their Compilation and Quality - Dobb, Maurice; Grossman, Gregory (Econometrica, 1962)
This study inquires into the reliability and general usability of Soviet statistics of the physical output of industrial commodities, with particular reference to the period beginning with the Five-Year Plans.